2019
DOI: 10.1186/s12879-019-4361-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis among HIV infected individuals on long term antiretroviral therapy in private healthcare sector in Pune, Western India

Abstract: Background Despite rapid scale up of antiretroviral therapy (ART), Tuberculosis (TB) remains the commonest opportunistic infection and cause of death among HIV infected individuals in resource limited settings like India. Incidence of TB in individuals on ART in private healthcare sector in India is infrequently studied. Methods This retrospective cohort study conducted between 1st March 2009 and 1st March 2017 aimed to evaluate rate of incident TB in individuals initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 45 publications
6
33
0
1
Order By: Relevance
“…According to this study, CD4 count was identified as a determinant factor for TB in which patients with a CD4 count of 201–349 cells/mm3 were more likely to develop TB after ART initiation as compared with those with a CD4 count of ≥350 cells/mm3 (AOR: 3.383 95% CI: 1.520, 7.528). It is consistent with a retrospective cohort study conducted in India in which patients with a CD4 count of <200 cells/mm3 were at higher risk to develop TB after ART initiation as compared with those with a CD4 count of >500 cells/mm3 [ 29 ]. It is also consistent with a retrospective longitudinal study conducted in Ethiopia in which patients with a CD4 count of >350 cells/mm3 were at lower risk to develop TB [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…According to this study, CD4 count was identified as a determinant factor for TB in which patients with a CD4 count of 201–349 cells/mm3 were more likely to develop TB after ART initiation as compared with those with a CD4 count of ≥350 cells/mm3 (AOR: 3.383 95% CI: 1.520, 7.528). It is consistent with a retrospective cohort study conducted in India in which patients with a CD4 count of <200 cells/mm3 were at higher risk to develop TB after ART initiation as compared with those with a CD4 count of >500 cells/mm3 [ 29 ]. It is also consistent with a retrospective longitudinal study conducted in Ethiopia in which patients with a CD4 count of >350 cells/mm3 were at lower risk to develop TB [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Another important consideration is the fact that the cohort was followed in a private health-care facility. Thus, better management of TB in the private sector might have contributed to the findings of lower incidence rate of TB, as has been reported from India [17]. We noted that CD4 count at initiation of ART was not associated with risk of developing TB.…”
Section: Discussionsupporting
confidence: 70%
“…A more recent meta-analysis from Ethiopia reported a pooled TB incidence rate of 3.79 (95% CI: 2.03-5.55) per 100 person years based on 7 studies in patients who received ART and IPT [35]. Several reports have shown the complementary effects of ART and IPT in preventing the development of TB [15,17,36,37]. All our cohort participants received IPT and this could also contribute to the lower incidence of TB.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Sustainable Development Goals (SDG) and Joint United Nations Programme on HIV/AIDS (UNAIDS) have laid goals and targets to end AIDS epidemic by 2030 (1). One of the targets to achieve 2030 HIV targets is to achieve HIV viral suppression among People Living on HIV (PLHIV) who are on Antiretroviral Therapy (ART) (1).Tuberculosis (TB) among PLHIV is still a public health concern(2) which despite wide coverage of ART and other interventions to reduce TB among PLHIV, cause increased ill-health and death (3), thus posing threats towards achieving SDG goals.…”
mentioning
confidence: 99%